Mast Cells Are Mediators of Fibrosis and Effector Cell Recruitment in Dermal Chronic Graft-vs.-Host Disease - Strattan, Ethan; Palaniyandi, Senthilnathan; Kumari, Reena; Du, Jing; Hakim, Natalya; Huang, Timothy; Kesler, Melissa V.; Jennings, C. Darrell; Sturgill, Jamie L.; Hildebrandt, Gerhard C. (Frontiers in Immunology, 2019)
Allogeneic hematopoietic stem cell transplant (allo-HSCT) is often used to treat acute leukemia or defects of hematopoiesis. Its widespread use is hampered by graft-versus-host disease (GVHD), which has high morbidity and mortality in both acute and chronic subtypes. Chronic GVHD (cGVHD) occurs most frequently in skin and often is characterized by pathogenic fibrosis. Mast cells (MCs) are known to be involved in the pathogenesis of other fibrotic diseases. In a murine model of cGVHD after allo-HSCT, C57BL/6J recipients of allogeneic LP/J donor cells develop sclerodermatous dermal cGVHD which is significantly decreased in mast cell-deficient B6.Cg-KitW-sh/HNihrJaeBsmGlliJ recipients. The presence of MCs is associated with fibrosis, chemokine production, and recruitment of GVHD effector cells to the skin. Chemokine production by MCs is blocked by drugs used to treat cGVHD. The importance of MCs in skin cGVHD is mirrored by increased MCs in the skin of patients with dermal cGVHD. We show for the first time a role for MCs in skin cGVHD that may be targetable for preventive and therapeutic intervention in this disease.